Strengthening educational advancement for enrolled nurses: Developing a new program framework for Uganda. - Mwizerwa, Joseph (University of Salford, 2023)
Uganda has three pre-service program levels for entering nursing practice, the first of which is, the Enrolled Nurse (EN) and constitutes majority of Uganda’s nursing workforce. While these enrolled nurses constitute a substantial proportion of the nursing workforce and are the lowest on the qualification’s framework, their educational advancement opportunities remain limited. A host of barriers are implicated including unsuitable program schedules among others. Due to work and family commitments ENs find themselves unmatched to available programs which are supposed to target them. Most of the literature on EN educational advancement originates from High income countries, such as Australia, Canada, USA, and European countries. Within Uganda, a low-income country, there is a lack of understanding of the needs of ENs who struggle to access educational advancement programs. Therefore, this thesis explores ENs experiences, aspirations and needs with respect to advancing their nursing careers, hence generating new evidence for designing responsive education programs.